Inpatient management of community-acquired pneumonia at the European Gaza Hospital: a clinical audit. (21st February 2018) - Alyacoubi, Said; Abuowda, Yousef; Albarqouni, Loai; Böttcher, Bettina; Elessi, Khamis
Abstract: Background: Disease severity scores such as CURB-65 are often used to guide the management of patients with community-acquired pneumonia. Early and adequate empirical antibiotic treatment reduces mortality. The aim of this study was to examine the severity assessment and management of patients presenting with community-acquired pneumonia at the European Gaza Hospital in the Gaza Strip and to compare this to the best available evidence. Methods: Medical records of all patients admitted to the European Gaza Hospital with a diagnosis of community-acquired pneumonia between Dec 1, 2015, and March 31, 2016, were reviewed retrospectively. Clinical practice was compared with recommendations for severity assessment and the management of community-acquired pneumonia, as reported in guidelines by the National Institute for Health and Care Excellence and the American Thoracic Society. Ethical approval was obtained from the General Directorate of Human Resources. Findings: 141 patients were admitted to the European Gaza Hospital with community-acquired pneumonia during the study period. Records of 41 patients were missing or could not be retrieved. The mean age of patients was 55·9 years (SD 20·2). Blood urea and nitrogen concentrations were not documented for 48 (48%) patients, and respiratory rate was not documented for 73 (73%) patients. The CURB-65 score was determined only for 12 (12%) patients. Microbiological testing was done only for two (2%) patients. Although 18 different antibiotic regimens were used, 81 (81%) patients received a β-lactam plus macrolide combination therapy, either given alone (49 [49%] patients) or with another antibiotic (32 [32%] patients), which is in line with the recommendations for patients admitted to hospital with community-acquired pneumonia. 43 (43%) patients received anti-viral drugs, and 41 (41%) patients received corticosteroids. Interpretation: Clinicians were poorly adherent to current standards of care in severity assessment and management of community-acquired pneumonia. Moreover, the broad range of antibiotic regimes used, without microbiological guidance, was inappropriate and will have increased the risk of antibiotic resistance. A local evidence-based clinical practice guideline should be developed and implemented. Furthermore, the documentation system should be improved to enhance the continuity of care and clinical auditing. Funding: None.